Rare bird documentation form for Glaucous Gull at Lock and Dam 14 near Davenport in 1981 - Newlon, Michael C.et al (1981)
Rare bird documentation form for one to two Glaucous Gulls at Lock and Dam 14 near Davenport on January 4 and one on January 11, 1981. Epson - sheet feed